Fish Diversity with Seasonal Variation of Water Quality in Fisheries Reservoir, Chitwan - Khadka, Raju; Jha, Dilip Kumar; Rai, Sunila; Pandit, Narayan Prasad (Journal of Agriculture and Forestry University, 2025)
A study was conducted to compare the seasonal variation of fish diversity, water quality and catch per unit effort (CPUE) of Fisheries Reservoir in four seasons viz., spring, summer, autumn and winter from October, 2016 to September, 2017. Water and fish sampling were done monthly from 3 different sites (water inlet, mid part and near water outlet) of reservoir and grouped into four seasons and compared. A total of 17 fish species representing 7 orders and 11 families with 15 genera were found in reservoir. Cypriniformes was the dominating fish order representing a total of 7 species. A total of 14 species were recorded in the autumn season, 13 species in both the spring and summer seasons, and 10 species in winter season. The abundance and CPUE of fishes were significantly higher in spring season (184±57.2 no. of fishes and 7360±2288.7 fishes/day, respectively) as compared to other seasons. The water quality parameters, depth, water temperature, total ammonium nitrogen, and soluble reactive phosphorus were higher in summer season (150.0±2.9 cm, 29.2±0.8°C, 0.78±0.17 mg/L and 0.035±0.004 mg/L, respectively) whereas dissolved oxygen, total dissolved solids and electrical conductivity in winter season (4.4±0.2 mg/L, 135.7±0.3 mg/L and 272.6±0.5 μS/cm, respectively). The value of total nitrogen was higher in spring season (1.96±0.26 mg/L). The parameters Secchi disk visibility, pH, Total alkalinity, total phosphorus, nitrite nitrogen and chlorophyll-a were statistically similar in all four seasons. A high density of phytoplankton were observed in the summer season (373.3±17.6 no./L) while the density of zooplankton in the autumn season (160.0±19.3 no./L). Fish abundance declined with decreasing dissolved oxygen, total nitrogen, chlorophyll-a and zooplankton density while it rises with decreasing water depth, secchi disk visibility, total ammonium nitrogen and nitrite nitrogen. Most of the measured water quality parameters were in the desirable range for fish while the number of fish species decreased as compared to the previous studies. To restore fish diversity in the reservoir, habitat improvement through the management of water quality parameters, the stocking of native species, and the avoidance of fishing may be helpful.